CORRELATION SEMINAR FOR PRE-CLINICAL UNDERGRADUATE MEDICAL STUDENTS AT CHITWAN MEDICAL COLLEGE, NEPAL - Timilsina, Sameer (Journal of Chitwan Medical College, 2024)
In medical education, clinical correlations are tools that help students make the connection between fundamental science ideas and medical applications. Correlation seminars for pre-clinical medical students at Chitwan Medical College have been conducted for several years now. The main purpose of these seminars is to prepare students for careers as doctors by correlating the basic science subjects with clinical sciences, a disease condition, and provoking or promoting basic science learning. Correlation seminars are usually conducted upon completion of each human body system by integrated teaching of basic science subjects. The topic and learning objectives of the seminar are decided by members from all basic science subjects including the community medicine department during regular meetings. Ten groups each consisting of 10 students are formed and a group member from each group presents the assigned topic which is evaluated by allocated faculty members present during the correlation seminar.